Iron Oxide Mineralogy of Asnawa Soils, Sulaimani Province, Kurdistan region - Kafoor, Sherwan; Maulood, Carman Q. (Sulaimani Journal for Pure and Applied Sciences, 2015)
Forty soil samples from three different zones (A, B and C) in Asnawa area were studied to identify and characterize the forms of Fe oxides in the <2 mm soil fractions using chemical extractions and XRDA technique. Neither citrate dithionite nor aqua regia solution were not effective enough to extract free Fe oxides in the soil samples. The maximum amounts of Fe oxides obtained were when five successive treatments with aqua regia solution had done. Soils of the quarry area (zone A) contained the highest amount of Fe oxides followed by soils from zone B and C. They were ranged from 52.1%, 38.6% and 15.1% respectively. XRD traces of the studied soils showed peaks characteristics of magnetite at 0.297, 0.256, 0.210, 0.161 and 0.147 nm. Other peaks of hematite at 0.271 nm, and wustite (Fe(1-X)O at 0.88 were also present. Diffraction peaks of magnetite after a single treatment with citrate dithionite and aqua regia were still evident on the X-ray chart whereas the diffraction peaks of hematite and wustite were disappeared.
Keywords: Asnawa; aqua regia; citrate dithionite magnetite wustite